The role of labour markets in fiscal policy transmission - Meri Obstbaum (Bank of Finland, 2011)
This paper shows how frictions in the labour market shape the responses of the economy to government spending shocks. The open economy New Keynesian DSGE model is extended by labour market frictions of the Mortensen-Pissarides type and a detailed description of fiscal policy. The nature of offsetting fiscal measures is found to be critical for the effects of fiscal stimulus, due to the different effects of different tax instruments on the labour market. Specifically, shifting the debt-stabilizing burden towards distortionary labour taxes has detrimental effects on the labour market outcome and on overall economic performance in a flexible wage regime. The results show that wage rigidity increases the effectiveness of fiscal policy in the short term but leads to a worse longer term result including unemployment exceeding steady state levels. The analysis suggests that a closer look at the functioning of labour markets may help to identify fiscal policy transmission channels not captured by the standard New Keynesian model.
URN:NBN:fi:bof-20140807579
Keywords: 330